1986
DOI: 10.3181/00379727-183-42425
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Blood Glucose after Compound 48/80 Treatment Is Not Related to Hepatic Mast Cell Degranulation in Rats

Abstract: Blood glucose, hepatic glycogen, and the histological integrity of hepatic mast cells, were evaluated in anesthetized rats receiving iv injections of 0.125 mg/kg body weight compound 48/80 (a mast cell degranulator) and/or of 0.001 to 10.0 mg/kg body weight lodoxamide tromethamine (an inhibitor of mast cell degranulation). A nonglucogenic dose of lodoxamide, 0.00 1 mg/kg body weight, prevented dissipation of histochemically demonstrable fluorescence in mast cells (degranulation) without inhibiting compound 48/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…(10) Furthermore, it has been shown that degranulation of mast cells existing in the liver tissue of rats treated once with C48/80 is not associated with glycogen depletion in the tissue. (11) Braun et al (12) have reported that depletion of reduced glutathione (GSH) induces glycogenolysis, resulting in stimulated VC synthesis in isolated mouse hepatocytes. Chan et al (13) have shown that glycogenolysis is involved in VC synthesis accompanied with GSH consumption in isolated rat hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…(10) Furthermore, it has been shown that degranulation of mast cells existing in the liver tissue of rats treated once with C48/80 is not associated with glycogen depletion in the tissue. (11) Braun et al (12) have reported that depletion of reduced glutathione (GSH) induces glycogenolysis, resulting in stimulated VC synthesis in isolated mouse hepatocytes. Chan et al (13) have shown that glycogenolysis is involved in VC synthesis accompanied with GSH consumption in isolated rat hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…because it provides an expedient method for measuring relative differences in circulating glucose in a large number of blood samples from a large number of rats. 41 …”
Section: Experimental Modelmentioning
confidence: 99%